Metallicities of M Dwarf Planet Host Stars from Kepler, K2, and TESS Observed by APOGEE: Trends with Exoplanetary Radii and Orbital Periods - Fábio Wanderley; Katia Cunha; Diogo Souto; Verne V. Smith; Simone Daflon (The Astronomical Journal)
One important property in studying the exoplanet population is the host star metallicity ([M/H]). In this study, we derived stellar metallicities and oxygen abundances for 48 M dwarf stars using the near-infrared high-resolution spectra from the SDSS APOGEE survey and synthetic spectra computed in LTE. We also investigated the exoplanetary radii distribution for a larger sample of 246 exoplanets orbiting 188 M dwarf stars. The [M/H] versus [O/M] distribution obtained indicates that our sample is composed mainly of thin disk stars, which follow the behavior of the low-alpha sequence in the Milky Way thin disk. Small planets with radii smaller than 3 R _⊕ were found around stars with a range of metallicities (−0.6 < [M/H] < +0.3), while larger planets of the sample orbit only stars with [M/H]≥ 0.0. These results indicate that while small planets can form in different environments, larger planets preferentially form in metal-rich protoplanetary disks. Exoplanets with P _orb  < 4.3 days orbit on average more metal-rich stars than planets with longer periods. This threshold is smaller than that found for FGK stars (8–10 days) and might be related to M dwarfs having a smaller dust sublimation radius. The distribution of exoplanets with R _p  > 4 R _⊕ shows a concentration at orbital periods between 2 and 5 days, which may result from inward orbital migration. There is also a different behavior between single-detected exoplanets and planets from multiplanetary systems, with the latter being found on average around more metal-poor stars, and with planetary radii roughly up to 3 R⊕.